2021
DOI: 10.1021/acs.inorgchem.1c00076
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical CeO2@N–C Ultrathin Nanosheets for Efficient Selective Oxidation of Benzylic Alcohols in Water

Abstract: A monodisperse CeO 2 @N−C ultrathin nanosheet self-assembled hierarchical structure (USHR) has been prepared by metal−organic framework template methods. The uniform coating of nitrogen-doped carbon (N−C) layers could play an important role in the adsorption and activation of benzylic alcohol. The unique 3D hierarchical structure self-assembled by ultrathin nanosheets provided enough active sites for the catalytic reaction. Therefore, the CeO 2 @N−C USHR can afford excellent catalytic performance for selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Inspired by the excellent properties of CdS-3@DUT-52 in the activation of oxygen, the reaction was extended to the oxidation reaction of alcohols, since the resulting aldehydes are also important components of pharmaceutical intermediates. 57,58 Conventional catalytic methods rely heavily on heavy metals, resulting in economic and environmental burdens. In a typical experiment, CdS-3@DUT-52 converted benzylic alcohol to benzaldehyde with a yield of 66% (Table S3, † entry 1).…”
Section: Photocatalytic Oxidation Of Alcoholsmentioning
confidence: 99%
“…Inspired by the excellent properties of CdS-3@DUT-52 in the activation of oxygen, the reaction was extended to the oxidation reaction of alcohols, since the resulting aldehydes are also important components of pharmaceutical intermediates. 57,58 Conventional catalytic methods rely heavily on heavy metals, resulting in economic and environmental burdens. In a typical experiment, CdS-3@DUT-52 converted benzylic alcohol to benzaldehyde with a yield of 66% (Table S3, † entry 1).…”
Section: Photocatalytic Oxidation Of Alcoholsmentioning
confidence: 99%
“…Thanks to the oxygen vacancy, reducible oxides are widely used in oxidation-involved heterogeneous catalytic reactions. For example, Liu et al found that CeO 2 nanorod exhibits superior catalytic performance in the oxidation coupling of alcohol and amine, and they proposed the promising catalytic performance was closely related to a significant number of oxygen vacancies and an appropriate interaction between CeO 2 and the carbon support . In addition to CeO 2 , MnO 2 is another typical representative of reducible oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Among various supports, carbon materials were still ideal supports of Pd due to their good corrosion resistance, excellent thermal stability and good chemical inertness ( Wang et al, 2022 ; Zhou et al, 2022 ). Recently, nitrogen doped material demonstrated fantastic catalytic performance in various fields ( Siuzdak et al, 2015 ; Wang et al, 2017 ; Wang et al, 2019 ; Lobiak et al, 2020 ; Shi et al, 2020 ), especially in the heterogeneous catalytic hydrogenations or oxidations ( Xu et al, 2012 ; Lu et al, 2019 ; Hao et al, 2021 ; Wang et al, 2021 ). The incorporation of nitrogen atoms into carbon materials or metal oxide had a significant impact on the chemical and electronic properties of metal catalysts, such as dispersion and electronic densities of metal nanopaticle, chemical state, active sites, etc ( Cui et al, 2016 ; Shen et al, 2020 ; Mao et al, 2019 ; von Deak et al, 2012 ; Wood et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%